Structure-Transport relationship in organized soft matter systems by diffusion NMR - Hazelbaker, Eric; Katihar, Aakanksha; Sanders, Monica; Menjoge, Amrish; Vasenkov, Sergey (Diffusion Fundamentals, 2011)
In this paper we demonstrate and discuss the potentials of pulsed field gradient nuclear magnetic resonance (PFG NMR) at high magnetic field and high magnetic field gradients for uncovering the relationship between the structural and transport properties of soft matter systems. The reported diffusion studies are focused on room temperature ionic liquids and their mixtures with carbon dioxide or water as well as on multicomponent lipid bilayers. Both types of systems exhibit a well-defined structural organization on various length scales. Our experimental approach allows correlating this structural organization with the transport properties. The diffusion data were obtained by proton and carbon-13 PFG NMR. The experimental studies were in some cases complemented by dynamic Monte Carlo simulations.